Identification and bioinformatics analysis of cilia-associated gene families in Euplotes amieti (Ciliophora, Hypotrichia) - Shen, Liheng; Xiong, Xiaobing; Xu, Zixiang; Liu, Yingli; Sheng, Yan; Sheng, Xin (Frontiers in Microbiology, 2025)
IntroductionCiliates serve as pivotal model organisms for investigating the protein composition and regulatory mechanisms underlying cellular processes. This study systematically explores the structural and functional characteristics of cilia-associated genes in Euplotes amieti, aiming to elucidate their roles in ciliogenesis and cilia-related pathways.MethodsThe macronuclear genome of E. amieti was sequenced using next-generation sequencing (NGS). Cilia-associated genes were identified via BLASTP analysis against homologs in hypotrich ciliates (Euplotes octocarinatus, Stylonychia lemnae, and Oxytricha trifallax). Functional annotations, including Non-Redundant (NR) classification, Pfam domain prediction, and Gene Ontology (GO) enrichment, were performed. Pathway enrichment analysis identified associated metabolic and signaling pathways. Experimental validation included quantitative polymerase chain reaction (QPCR) of cilia-related gene families, RNA interference (RNAi) targeting ARL2BP and DYNLRB2, and immunofluorescence staining to assess microtubule arrangement.ResultsA total of 418 cilia-associated genes were identified, with 44 conserved across the four hypotrich ciliate species. Functional categorization revealed kinases, dyneins, tubulins, and autophagy-related proteins. Pfam annotations predicted three conserved domains. GO terms were enriched in tubulin binding, cilia assembly, and microtubule-based movement. Pathway analysis implicated these genes in adenine ribonucleotide biosynthesis, glycolysis/gluconeogenesis, Wnt, and AMP-activated protein kinase (AMPK) signaling. QPCR showed significant downregulation of cilia-related proteins during mitosis. RNAi of ARL2BP and DYNLRB2 increased mortality, reduced motility, and disrupted cortical microtubule organization via immunofluorescence. Thirty-nine hub genes were strongly linked to ciliopathies.DiscussionCilia-associated genes in E. amieti are integral to DNA replication, energy metabolism, intercellular communication, and morphogenesis. The conserved hub genes associated with ciliopathies suggest evolutionary preservation of ciliogenesis regulation. ARL2BP and DYNLRB2 are functional important in ciliary dynamics and structural integrity. This study provides crucial insights into the roles of cilia-associated genes in ciliates, advancing understanding of ciliogenesis mechanisms and their implications for ciliopathy research.